Reduction of total chromium levels from raw tannery wastewater via electrocoagulation using response surface methodology - Aguilar Ascón, Edwar (2019)
This study focused on reducing total chromium levels in raw wastewater from the leather tanning industry via electrocoagulation to comply with maximum permissible limits (MPL) and to determine the effects of main process parameters. An electrocoagulation reactor was built using aluminum electrodes as an anode and cathode. Then, the response surface methodology was applied using a 3k factorial design considering three factors, namely current intensity, treatment time, and pH. The total chromium removal percentage was considered as a response variable. 99% of the total chromium found in wastewater could be removed after 14-min treatment at 2-A current intensity and pH 5.5. Similar amount of chromium was removed at pH of 8.5 and 7. Statistical analysis performed at a confidence level of p < 0.05 revealed that all three factors influenced electrocoagulation. Total chromium could be efficiently removed from raw wastewater at a current intensity of 2.9 A, a pH of 8.4, and a treatment time of 21 min, suggesting that electrocoagulation using aluminum electrodes is an efficient method for total chromium removal. Thus, this process must be considered as a solution to the problems caused by the leather tanning industry and for better compliance with the MPL established in the Peruvian environmental standards.